2023
DOI: 10.1242/dev.200436
|View full text |Cite
|
Sign up to set email alerts
|

Ikaros family proteins redundantly regulate temporal patterning in the developing mouse retina

Abstract: Temporal identity factors regulate competence of neural progenitors to generate specific cell types in a time-dependent manner, but how they operate remains poorly defined. In the developing mouse retina, the Ikaros zinc finger transcription factor Ikzf1 regulates production of early-born cell types, except cone photoreceptors. In this study we show that, during early stages of retinal development, another Ikaros family protein, Ikzf4, functions redundantly with Ikzf1 to regulate cone photoreceptor production.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…However, under ironmediated stress conditions or exposure to high concentrations for prolonged periods of time, Lcn2 may increase cell death in neurons and astrocytes [59,60]. Ikzf4 together with Ikzf1 have been identified as neuronal reprogramming factors, having been shown to reprogram fibroblasts into induced neurons and convert uninjured retinal into neuronlike cells [67,68]. The glycoprotein Chi3l1 is predominantly expressed by astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, under ironmediated stress conditions or exposure to high concentrations for prolonged periods of time, Lcn2 may increase cell death in neurons and astrocytes [59,60]. Ikzf4 together with Ikzf1 have been identified as neuronal reprogramming factors, having been shown to reprogram fibroblasts into induced neurons and convert uninjured retinal into neuronlike cells [67,68]. The glycoprotein Chi3l1 is predominantly expressed by astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that the miR-128 expression was significantly lower in patients with Ikzf1 deletion than those without Ikzf1 deletion in B-cell precursor acute lymphoblastic leukemia ( Krzanowski et al, 2017 ). Importantly, these hub genes not only participate in immune regulation but also play important roles in neurodegenerative diseases through the ceRNA network regulation ( Javed et al, 2023 ; Yi et al, 2023 ). Qin et al (2023) revealed that miR-6734-3p and its target mRNA Cyth4 expression were correlated with patients’ age in Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the percentage of Nr2e3+Crx+ cells was identical (S6Q Fig) . Therefore, the loss of cones in Hes1 mutants cannot be attributed to accelerated rod genesis. Another explanation is that Hes1 provides temporal restriction to the Otx2 lineage to prevent prenatal bipolar neuron formation [100]. Alternatively, RGC development may accelerate in the absence of Hes1, depleting the availability of transitional RPCs to activate Otx2 and adopt a cone fate.…”
Section: Plos Geneticsmentioning
confidence: 99%